Doppelgänger analysing 'doubles' across antiquity, fiction, psychopathology and neuroscience - Oyebode, Femi 1954- (Cambridge medicine (Series), 2025)
The concept of doppelgänger, or 'double' - a conceived exact but sometimes invisible replica of a living person - has fascinated and intrigued people for centuries. This notion has a long history and is a widespread belief among cultural groups around the world. Doppelgängers have influenced literature and cinema, with writers such as Fyodor Dostoyevsky and Robert Louis Stevenson, and directors like Alfred Hitchcock exploring the phenomenon to great effect. This book brings together the literary and cinematic with empirical scientific literature to raise fundamental questions about the nature of the self and the human mind. It aims to establish the experience of the self and unravel the brain processes that determine bodily representation and the errors that make possible the experience of the doppelgänger phenomenon. This book will appeal to psychiatrists, neurologists, and neuroscientists, as well as interested general readers